U źródeł włoskiej geopolityki. Traktat Giacomo Durando O włoskiej narodowości z 1846 roku wraz z tłumaczeniem i opracowaniem krytycznym Avvertimeno dell’Autore .......... 91 (Riflessioni intorno alla storia politica d’Italia = Refleksje wokół historii politycznej Włoch, 2025)
AT THE ORIGINS OF ITALIAN GEOPOLITICS: GIACOMO DURANDO’S TREATISE ON ITALIAN NATIONALITY (1846) WITH TRANSLATION AND CRITICAL COMMENTARY (AVVERTIMENTO DELL’AUTORE [IN:] DELLA NAZIONALITÀ ITALIANA. SAGGIO POLITICO-MILITARE DI GIACOMO DURANDO DA MONDOVÌ, LAUSANNE 1846)Stefan Bielański’s study provides an in-depth examination of the geopolitical determinants of Italian unification, whereas the critical edition of the introduction to General Giacomo Durando’s treatise Della nazionalità italiana highlights the articulation of Italian national ideas in relation to the nascent geopolitical paradigms of the risorgimento.